AUTOPATHOGRAPHY AS THE REPRESENTATION OF OUTLOOK PECULIARITIES OF MODERN SOCIETY - Самойленко, Елена (SWorldJournal, 2020)
The article is devoted to autopathography as to one of the representation of the remission society, which has become very popular at the beginning of the XXI century. The author proves that autopathography is the realization of one peculiarity of the mod